Microarray and pathway analysis reveals decreased CDC25A and increased CDC42 associated with slow growth of BCL2 overexpressing immortalized breast cell line - Long, Jacquelyn M.; Bell, Charles W.; Fagg, W. Samuel IV; Kushman, Mary E.; Becker, Kevin G.; McCubrey, James A.; Farwell, Mary A. (East Carolina University, 2008)
Bcl-2 is an anti-apoptotic protein that is frequently overex-pressed in cancer cells but its role in carcinogenesis is not clear. We are interested in how Bcl-2 expression affects non-cancerous breast cells and its role in the cell cycle. We prepared an MCF10A breast epithelial cell line that stably overexpressed Bcl-2. We analyzed the cells by flow cytometry after synchronization, and used cDNA microarrays with quantitative reverse-transcription PCR (qRTPCR) to determine differences in gene expression. The microarray data was subjected to two pathway analysis tools, parametric analysis of gene set enrichment (PAGE) and ingenuity pathway analysis (IPA), and western analysis was carried out to determine the correlation between mRNA and protein levels. The MCF10A/Bcl-2 cells exhibited a slow-growth phenotype compared to control MCF10A/Neo cells that we attributed to a slowing of the G1-S cell cycle transition. A total of 363 genes were differentially expressed by at least two-fold, 307 upregulated and 56 downregulated. PAGE identified 22 significantly changed gene sets. The highest ranked network of genes identified by IPA contained 24 genes. Genes that were chosen for further analysis were confirmed by qRT-PCR, however, the western analysis did not always confirm differential expression of the proteins. Downregulation of the phosphatase CDC25A could solely be responsible for the slow growth pheno-type in MCF10A/Bcl-2 cells. Increased levels of GTPase Cdc42 could be adding to this effect. PAGE and IPA are valuable tools for microarray analysis, but protein expression results do not always follow mRNA expression results. Originally published Cell Cycle, Vol. 7, No. 19, Oct. 2008
Keywords: Breast cells; Microarrays; Anti-apoptotic protein